Best Practices for Increasing Employee Engagement and Completion Rates in Online Courses: A Case Study on Creating a Culture of Learning - Buckley, Claudia; Castro Jorge, Maria Fernanda (International Journal of Advanced Corporate Learning (iJAC), 2024)
This case study examines how the human resource department at the target company used features of their learning management system (LMS) to successfully implement a learning and development (L&D) program where employees were motivated not only to engage with courses in a meaningful way but also to complete them at a rate that was higher than that typically seen for eLearning courses. The research discusses the results of a study on the case organization and presents the implications of the findings.